Incorporation of environmental issues in South Africa's municipal Integrated Development Plans. Issue 1 (2nd January 2016) - Ruwanza, Sheunesu; Shackleton, Charlie M.
Abstract : The transition to full democracy in South Africa in 1994 saw local government becoming the focal point for dealing with socio-economic development needs of communities. The Integrated Development Plan (IDP) has been used as the tool for guiding local development objectives, balanced against environmental demands within a sustainable development paradigm. Here we examine the extent to which this is being achieved through an analysis of IDPs from 35 different municipalities at three scales. We test the hypothesis that the metropolitan municipalities are better at mainstreaming environmental issues into their IDPs than local and district municipalities. Results indicate that mainstreaming environmental issues in IDPs is still low. The hypothesis that metropoles are better at mainstreaming environmental issues than district and local municipalities was not accepted since there were no significant differences between municipalities. There was low relative budget allocations and inclusion of vision and mission statements that mainstream environmental issues in all municipalities. For mainstreaming of environmental issues to be effective in IDPs, both proactive approaches and multi-faceted bottom-up and top-down approaches are suggested.